Carbohydrates for improving the cognitive performance of independent-living older adults with normal cognition or mild cognitive impairment (review). - Ooi, Cheow Peng; Loke, Seng Cheong; Yassin, Zaitun; Tengku Abdul Hamid, Tengku Aizan (EBSCO Publishing, 2011)
BACKGROUND: Mild cognitive impairment (MCI) is an intermediate state between normal cognition and dementia in which daily function is largely intact. This condition may present an opportunity for research into the prevention of dementia. Carbohydrate is an essential and easily accessible macronutrient which influences cognitive performance. A better understanding of carbohydrate-driven cognitive changes in normal cognition and mild cognitive impairment may suggest ways to prevent or reduce cognitive decline. OBJECTIVES: To assess the effectiveness of carbohydrates in improving cognitive function in older adults. SEARCH STRATEGY: We searched ALOIS, the Cochrane Dementia and Cognitive Improvement Group Specialized Register on 22 June 2010 using the terms: carbohydrates OR carbohydrate OR monosaccharides OR disaccharides OR oligosaccharides OR polysaccharides OR CARBS. ALOIS contains records from all major healthcare databases (The Cochrane Library, MEDLINE, EMBASE, PsycINFO, CINAHL, LILACS) as well as from many trial databases and grey literature sources. SELECTION CRITERIA: All randomised controlled trials (RCT) that have examined the efficacy of any form of carbohydrates in normal cognition and MCI. DATA COLLECTION AND ANALYSIS: One review author selected and retrieved relevant articles for further assessment. The remaining authors independently assessed whether any of the retrieved trials should be included. Disagreements were resolved by discussion. MAIN RESULTS: There is no suitable RCT of any form of carbohydrates involving independent-living older adults with normal cognition or mild cognitive impairment.